The Implementation of Notary Responsibility Association in the Online Administration System - Sejati, Hono; Suryandari, Wieke Dewi (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
This study aims to analyze procedure for registering associations is through the online Legal Entity Administration System. 2) The role and responsibilities of a notary in carrying out the registration of associations through the online Legal Entity Administration System. The approach method in this research is a sociological juridical approach. The data used are primary data and secondary data obtained through interviews and literature study, data analysis was carried out in a descriptive analytical manner. The conclusion show the association registration procedure through the online Legal Entity Administration System is uncomplicated. The procedure begins with an application for ordering the name of the association through SABH www.ahu.go.id, then the application for legalization of the association's legal entity must be submitted by a notary with supporting documents submitted electronically. Supporting documents in the form of an electronic statement from the applicant. A statement letter containing the completeness of the association's establishment documents from the applicant. The Ministerial Decree concerning the legalization of the legal entity association is issued no later than 14 days. The period of time is calculated from the date of the statement of no objection from the Minister. The fee for ordering the name of the association is IDR 100,000, -, while for the ratification of the establishment of the association of IDR 250.000,-. 2). The role of the notary in carrying out the registration of associations through the online legal entity administration system is to order names and register the ratification of the association to the minister through the SABH. Notaries have an important role in managing the legal entity of the Association. People who need the legal entity ratification of the Association cannot access the SABH directly but must go through a Notary who has been registered in the SABH. This is because the notary plays a role in carrying out statutory orders so that the interests of the parties do not violate the law.